On the Cause of US’s Abstaining from Voting for UN Security Council Resolution 2728 (2024) - Maulana, Muhammad Alfian (Journal of Islamic World and Politics, 2024)
This study examined the rationale behind the United States (US) abstention from UN Security Council (UNSC) Resolution 2728, March 25, 2024, which called for a ceasefire in the Israel-Palestine conflict. This research used the Politics of Absence theory to explain the motives behind the abstention. The framework drew on Suzanne Dovi's Typology of Absence, which provides a foundation for understanding strategic objectives such as protection, protest, and partition, which explain state abstention in international voting. With a qualitative approach, this study found that the US decision was driven by the protection of national interests, dissatisfaction with the failure of the resolution to condemn Hamas, and an inclination to explore alternative conflict resolution mechanisms.